Characterization and Treatment of Medical Laboratory Wastewater by Ozonation: Optimization of Toxicity Removal by Central Composite Design - Basturk, Irfan; Varank, Gamze; Murat-Hocaoglu, Selda; Yazici-Guvenc, Senem; Oktem-Olgun, Elmas Eva; Canli, Oltan (TAYLOR & FRANCIS INC, 2021)
This study performed a long-term characterization of medical laboratory wastewaters (MLWs) arising from diagnosis and examination units. The results indicated that the MLWs may be assessed as strong domestic wastewater and also have highly toxic properties. Furthermore, statistical optimization of toxicity removal through ozonation was investigated using the central composite design. COD, BOD5, AOX, and Toxicity unit (TU) removals were determined to be 50.6%, 43.2%, 48.9%, and 99.9%, respectively. The TU value of the MLW decreased from 163 to 0.16. The results of the study indicated that the ozonation process is an effective treatment option for COD, BOD5, AOX, and TU removal from MLW.
Keywords: Ozonation; medical laboratory wastewater; characterization; toxicity; central composite design; RESPONSE-SURFACE METHODOLOGY; HOSPITAL EFFLUENTS; BISPHENOL-A; OXIDATION; OZONE; PHARMACEUTICALS; DISINFECTION; DEGRADATION; SEWAGE; Engineering; Environmental Sciences & Ecology